A comparative study of three approaches of assertiveness training in the reduction of interpersonal anxiety and in the improvement of interpersonal relationship skills and assertive behavior - Loyola, Salvacion C. (Animo Repository, 1984)
This study examines whether interpersonal anxiety can be reduced and interpersonal relationship skills and assertive behavior be improved by assertiveness training. Eighty-four freshmen college students enrolled at Don Mariano Marcos Memorial State University were randomly distributed into each of four treatment conditions: cognitive counseling, social skills training, combined treatment, and wait-list no treatment control group. The participants were found to be low assertive based on Rathus Assertiveness Schedule (RAS) and Gambrill and Richey Assertionn Inventory (GRAI) and low in interpersonal skills based on Interpersonal Relationship Skills Inventory (IRSI) and GRAI, and having interpersonal anxiety as found our through GRAI. The experimental method of research used was a modified pretest-posttest control group design (Campbell & Stanley, 1963) where the 3 experimental groups were tested before and after treatment the wait-list no-treatment control group was given pretest and posttest only. Each of the 3 treatment groups was given 5 consecutive training days with a total of 14 hours. The wait-list no-treatment control group was not given any training but waited for another semester. Counterconditioning effect on interpersonal anxiety was based on the difference (gain score) between posttest and pretest on GRAI, RAS, and IRSI. Pretest score was used as covariate and gain score as covariate for computing ANCOVA. Significance of difference was tested at .05 level. Post hoc comparisons between pair of means were made using Duncan's Multiple Range Test. Results showed that among the 4 treatment conditions there is a significant difference in effecting the reduction of interpersonal anxiety and in the improvement of interpersonal relationship skills and assertive behavior. Adverse comparisons revealed that: 1) there is no significant difference between cognitive counseling and social skills training in all measures; 2) no significant difference between the separate administration of cognitive counseling and social skills training compared to the combined administration of the 2 treatments except in IRSI areas of sensitivity and empathy and effective group work between cognitive counseling and combined; 3) there is a significant difference between each of the 3 treatment groups compared to the wait-list no-treatment control group except in IRSI area of communication between cognitive counseling and control and IRSI area of sensitivity and empathy between combined and control; and 4) participants assessed treatment program as much in development of ideas, in meeting of expectations, and in gaining knowledge and skills. Conclusions arrived at were: 1) In the reduction of interpersonal anxiety and in the improvement of interpersonal relationship skills and assertive behavior any of the 3 approaches of assertiveness training: cognitive counseling, social skills training, and combined treatment can be used with relatively equal effectiveness. 2) Any of the 3 training programs can be used with interpersonally anxious and low assertive college students for development of new ideas, knowledge and skills.